Design Sprint versus Design Thinking: A comparative analysis - Figueiredo, Lucas Baraças; Fleury, André Leme (Revista Gestão da Produção Operações e Sistemas, 2019)
Context: Design Sprint (DS) is a new design methodology for designing new products that resembles Design Thinking (DT) in designing solutions that diverge and focus on the problem and solution fields, to be then tested in prototypes. Yet it differs from DT by incorporating Lean Startup concepts such as agility and elimination of costly or low-value activities. Although it gained increased interest in the organizational world, it is still unexplored in the literature, without an analysis of best practices, and how this process may be more appropriate than traditional DT processes. Objective: In spite of the improvements proposed by the design community to the original process, this study aims to perform a comparative analysis of the DS process, as prescribed in the book that originated the methodology, against traditional DT processes, considering its phases and techniques , and what the advantages and disadvantages of each methodology are. Method: The research used the methodological approach of multiple case study by evaluating three DS processes in a company that executes processes with both methodologies. In addition to observing the processes and documenting the decisions made, six interviews were conducted with company partners and experts from the area, who participated in the processes. Results: The article describes the execution of DS processes in detail and then summarizes the advantages of these processes against DT processes, such as: low experimentation barrier, alignment with high management for continuing the work, orientation to incremental innovations. Nevertheless, the coexistence of the two methodologies is proposed, such that DS can be more efficient when used as an initial stage of requirements of new products, while DT proves to be more useful as a methodology for generating new ideas. Conclusion: The research on theoretical and practical contributions by investigating a topic not yet explored in the literature, positioning positive and negative aspects of DS in relation to other more established design methodology (DT), and suggesting how these methodologies can be applied more efficiently to creating new products and services.